Pengembangan E-Learning Management System Untuk Tingkat Sekolah Dasar Berbasis Website dengan Metode Agile - Eka Permana Putra; Agung Triayudi; Agus Iskandar (Journal of Information System Research (JOSH), 2023)
Information Technology has played an important role as a medium of information and communication in the field of education, one of which is in the Academic Management of Schools. In the world of educational technology it is not only related to the internet but can also be seen from the system or how to teach in schools. At present, the learning process using E-learning can be interactive so that students are able to interact with technology as a learning medium. Web-based learning media (e-learning) is a web that can help educators in the rapidly developing era of information and communication technology development. In this research, the problem that arises in the school environment is that there is no special place for students and teachers to be organized in obtaining learning materials and collecting assignments, documentation of knowledge of learning materials that are not stored properly, so it takes a long time to find the required knowledge back. Therefore used data collection methods, namely the method of observation, interview methods (interviews), and literature study. The Agile method is the most appropriate method used to design this system with the aim that the author can help ease the task of students and teachers in carrying out their duties. The results achieved in making the e-learning application at SDN Tengah 01 KramatJati are that students can understand material without a time limit, consult, take quizzes, upload assignments and can immediately see their learning results in person, while teachers can upload material, create questions and give them directly live.